1997
DOI: 10.1097/00007890-199706270-00025
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Aspects of Liver Aeration by Vascular Persufflation With Gaseous Oxygen

Abstract: Our results indicate that the oxygen concentration of the persufflation gas rather than the persufflation pressure is a determinant of successful tissue oxygenation during cold storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Minor et al [14,42] showed in their studies involving liver preservation that VSOP can provide energetic homeostasis by elevated ATP tissue concentrations and a normalized redox status leading to reduced lipid peroxidation. Here, in our VSOP group, a higher GSH/GSSG ratio and reduced lipid peroxidation as reflected in lower tissue TBARS concentrations were observed compared to the OMP group.…”
Section: Discussionmentioning
confidence: 99%
“…Minor et al [14,42] showed in their studies involving liver preservation that VSOP can provide energetic homeostasis by elevated ATP tissue concentrations and a normalized redox status leading to reduced lipid peroxidation. Here, in our VSOP group, a higher GSH/GSSG ratio and reduced lipid peroxidation as reflected in lower tissue TBARS concentrations were observed compared to the OMP group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the influence of continuous oxygenation of the grafts should be isolated by nonperfusion related aeration of the liver by mere gaseous oxygen insufflation during hypothermic storage, as was proposed earlier [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…These reports and the present study show that the granulosa cells and oocytes are exposed to suboptimal conditions and are injured by ischemic conditions. Generally, one of the key factors in organ preservation is restoration of the ATP concentration in the tissues during preservation [9,21]. It has been shown that maintaining the preservation solution at a low temperature is beneficial for restoring the developmental competence of oocytes obtained from ovaries preserved for a long period of time [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%